130k views
4 votes
8x - 3(x - 1) = 2x + 6 solve for x and show work

User Oreopot
by
5.2k points

2 Answers

4 votes

Answer:

x = 3

Explanation:

8x - 3(x - 1) = 2x + 6

simplify

8x - 3x + 3 = 2x + 6

add like terms

5x + 3 = 2x + 6

subtract 2x from both sides

3x + 3 = 6

subtract 3 from both sides

3x = 3

divide by 3

x = 3

User CrouZ
by
5.1k points
7 votes

Answer:

x= 1

Explanation:

open brackets first

8x - 3x + 3 = 2x + 6

Calculate

5x+3= 2x+6

transpose the like terms

5x-2x= 6-3

calculate

3x= 3

x= 3/3

x= 1

User Serina
by
5.1k points